LITERACY INITIATIVE IN ISLAMIC BOARDING SCHOOL - Zurriat Nyndia Rahmawati; Afriandi Setiawan; Muhammad Rizal Akbar Zamzami; Nadifa Rahma (Faculty of Letters Universitas Abdurachman Saleh Situbondo, 2025)
Literacy is one of the key skills for the students. Unfortunately, it was found that the students of Al-Islahiyah Islamic boarding school had limited access to books and low reading motivation, which might inhibit the development of their literacy skill. The problem was addressed by literacy initiative which was done with the aim at increasing reading literacy skill of the students in Al-Islahiyah Islamic boarding school. The programs were done through four stages, which were 1) needs analysis, 2) program planning, 3) program implementation, and 4) program evaluation. In the program implementation stage, there was a workshop of reading, in which the students were introduced to various genres of text and discussed the summary of the books. Then, the program was continued by the formation of reading club. The reading club was done twice a week in the library during study time. This literacy initiative was successful in building reading habit in the boarding school. In the future, it is expected that the program can continue to strive to increase the literacy skill of the students.